The legality of establishment of political parties for religious minorities in Islam - Muhammad Husni, Ahmad; Muhammad Husni, Amin (Zes Rokman Resources, 2024)
This study discusses an important aspect of political rights for religious minorities in Islam. The problem of the study lies on the legality of forming political parties for religious minorities in the Islamic state. The study aims to demonstrate the extent of tolerance of Islam and acceptance of others, and to explain that the basis of dealing of the Islamic state with all its citizens is equality. The study adopts an inductive approach to collect materials on jurisprudence, and the analytical method to analyze views and evidence of responding to them. The study reaches to several results, most notably of which is the legality of forming political parties for religious minorities in the Islamic state under certain conditions, and this is consistent with the purpose and interest of the Islamic law.